Scoping reviews in health professions education: challenges, considerations and lessons learned about epistemology and methodology - Thomas, Aliki; Lubarsky, Stuart; Varpio, Lara; Durning, Steven J.; Young, Meredith E. (Advances in health sciences education : theory and practice, 2020)
Scoping reviews are increasingly used in health professions education to synthesize research and scholarship, and to report on the depth and breadth of the literature on a given topic. In this Perspective, we argue that the philosophical stance scholars adopt during the execution of a scoping review, including the meaning they attribute to fundamental concepts such as knowledge and evidence, influences how they gather, analyze, and interpret information obtained from a heterogeneous body of literature. We highlight the principles informing scoping reviews and outline how epistemology —the aspect of philosophy that “deals with questions involving the nature of knowledge, the justification of beliefs, and rationality”—should guide methodological considerations, toward the aim of ensuring the production of a high-quality review with defensible and appropriate conclusions. To contextualize our claims, we illustrate some of the methodological challenges we have personally encountered while executing a scoping review on clinical reasoning and reflect on how these challenges could have been reconciled through a broader understanding of the methodology’s philosophical foundation. We conclude with a description of lessons we have learned that might usefully inform other scholars who are considering undertaking a scoping review in their own domains of inquiry.